Fluoride ion secondary battery
The fluoride ion secondary battery was solved by using a composite fluoride of copper and fluoride compound and a composite of doped lanthanide fluoride and carbon material in a fluoride ion secondary battery, combining nanoparticles of BaCaF4 and SrCaF4. The problem of insufficient discharge capacity and energy density improves the performance and safety of the battery.
Patent Information
- Application Number
- CN202210021117.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-03-03
- Filing Date
- 2022-01-10
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-01-10
AI Technical Summary
The discharge capacity and energy density of existing fluoride ion secondary batteries are insufficient, and there are safety hazards for flammable organic solvents in the electrolyte of lithium ion secondary batteries.
A fluoride ion secondary battery was designed, using a composite fluoride of copper and fluoride compound as the positive electrode active material, the negative electrode layer contains a composite of doped lanthanide fluoride and carbon material, and the solid electrolyte layer uses BaCaF4 and SrCaF4. nanoparticles improve ion and electron conductivity.
The discharge capacity and energy density of fluoride ion secondary batteries are significantly improved, and the safety and performance of the batteries are enhanced.
Smart Images

Figure HDA0003462637190000011
Abstract
Description
Technical Field
[0001] The invention relates to a fluoride ion secondary battery. Background Art
[0002] Conventionally, lithium ion secondary batteries are widely used as secondary batteries having high energy density. In lithium ion secondary batteries, a separator is arranged between a positive electrode and a negative electrode, and an electrolyte is filled therein.
[0003] The electrolyte of a lithium ion secondary battery generally contains a flammable organic solvent, and therefore safety against heat may become a problem.
[0004] Therefore, fluoride ion secondary batteries are being studied as all-solid batteries in which a solid electrolyte layer is disposed between a positive electrode layer and a negative electrode layer.
[0005] It is known to use a composite fluoride of a metal and a fluorine compound as a positive electrode active material for a fluoride ion secondary battery (for example, see Patent Document 1).
[0006] [Prior Technical Literature]
[0007] (Patent Document)
[0008] Patent Document 1: International Publication No. 2019 / 187942 Summary of the invention
[0009] [Problems to be solved by the invention]
[0010] However, further improvement in the discharge capacity and energy density of fluoride ion secondary batteries is desired.
[0011] An object of the present invention is to provide a fluoride ion secondary battery having excellent discharge capacity and energy density.
[0012] [Technical means to solve the problem]
[0013] One aspect of the present invention is a fluoride ion secondary battery comprising a positive electrode layer, a solid electrolyte layer and a negative electrode layer, wherein the positive electrode layer comprises a positive electrode active material, the positive electrode active material comprises a composite fluoride of copper and a fluorine compound, the solid electrolyte layer comprises BaCaF4, the negative electrode layer comprises a negative electrode active material, a conductive aid and a solid electrolyte, the negative electrode active material comprises a lanthanide fluoride doped with an alkaline earth metal fluoride, the conductive aid comprises a carbon material, the solid electrolyte contained in the negative electrode layer comprises at least one of BaCaF4 and SrCaF4, and the lanthanide fluoride doped with an alkaline earth metal fluoride and the carbon material are composited.
[0014] The aforementioned lanthanide fluoride may also be one or more compounds selected from the group consisting of LaF3, CeF3, SmF3 and NdF3.
[0015] The aforementioned alkaline earth metal fluoride may be one or more compounds selected from the group consisting of CaF2, SrF2 and BaF2.
[0016] The lanthanide fluoride doped with alkaline earth metal fluoride may also be selected from La 0.9 Ba 0.1 F 2.9 、Ce 0.95 Ba 0.05 F 2.95 、Ce 0.95 Sr 0.05 F 2.95 Ce 0.95 Ca 0.05 F 2.95 More than one compound in the group consisting of.
[0017] The solid electrolyte included in the negative electrode layer may include nanoparticles of at least one of BaCaF 4 and SrCaF 4 .
[0018] The solid electrolyte layer may contain nanoparticles of BaCaF4.
[0019] (Effects of the Invention)
[0020] According to the present invention, a fluoride ion secondary battery having excellent discharge capacity and energy density can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The graph shows the initial charge and discharge curves of the all-solid fluoride ion secondary batteries of Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0022] Hereinafter, embodiments of the present invention will be described.
[0023] <Fluoride ion secondary battery>
[0024] The fluoride ion secondary battery of this embodiment has a positive electrode layer, a solid electrolyte layer, and a negative electrode layer. For example, a positive electrode current collector, a positive electrode layer, a solid electrolyte layer, a negative electrode layer, and a negative electrode current collector are arranged in this order.
[0025] [Negative electrode layer]
[0026] The negative electrode layer includes a negative electrode active material, a conductive aid and a solid electrolyte. Here, the negative electrode active material includes a lanthanide fluoride doped with an alkaline earth metal fluoride, the conductive aid includes a carbon material, and the solid electrolyte includes at least one of BaCaF4 and SrCaF4. In addition, the lanthanide fluoride doped with an alkaline earth metal fluoride and the carbon material are composited. That is, the negative electrode layer includes a composite of a lanthanide fluoride doped with an alkaline earth metal fluoride and a carbon material (hereinafter also referred to as a composite of a lanthanide fluoride and a carbon material).
[0027] The negative electrode layer includes lanthanum fluoride doped with fluorinated alkaline earth metals, so that ion conductivity is improved. In addition, the negative electrode layer includes a complex of lanthanum fluoride and carbon material, so that electronic conductivity is improved. Further, the negative electrode layer includes at least one of BaCaF4 and SrCaF4, so the defluorination potential is low. Therefore, the discharge capacity of the fluoride ion secondary battery of this embodiment is improved.
[0028] (Negative electrode active material)
[0029] The lanthanoid fluoride is not particularly limited, and examples thereof include LaF 3 , CeF 3 , SmF 3 , and NdF 3 . Two or more kinds of lanthanoid fluorides may be used in combination.
[0030] The alkaline earth metal fluoride doped with the lanthanoid fluoride is not particularly limited as long as it has ion conductivity, and examples thereof include CaF 2 , SrF 2 , and BaF 2 , and two or more thereof may be used in combination.
[0031] Examples of the lanthanide fluoride doped with alkaline earth metal fluoride include La 0.9 Ba 0.1 F 2.9 、Ce 0.95 Ba 0.05 F 2.95 、Ce 0.95 Sr 0.05 F 2.95 、Ce 0.95 Ca 0.05 F 2.95 etc., and two or more kinds may be used in combination.
[0032] The negative electrode active material may further contain a negative electrode active material other than lanthanoid fluoride doped with alkaline earth metal fluoride.
[0033] The negative electrode active material other than the lanthanoid fluoride doped with the alkaline earth metal fluoride is not particularly limited as long as it is a negative electrode active material that can be used for a fluoride ion secondary battery.
[0034] (Conductive additive)
[0035] The carbon material is not particularly limited as long as it has electron conductivity, and may be carbon black. Examples of carbon black include furnace black, Ketjen black, and acetylene black, and two or more thereof may be used in combination.
[0036] The conductive additive may further contain a conductive additive other than the carbon material.
[0037] The conductive aid other than the carbon material is not particularly limited as long as it is a conductive aid that can be used in a fluoride ion secondary battery.
[0038] (Composite of lanthanide fluoride and carbon material)
[0039] In the composite of lanthanoid fluoride and carbon material, for example, at least a portion of the surface of lanthanoid fluoride particles is coated with the carbon material.
[0040] The particle size of the composite of lanthanoid fluoride and carbon material is preferably 10 μm or less, more preferably 5 μm or less. When the particle size of the composite of lanthanoid fluoride and carbon material is 10 μm or less, ion conductivity and electron conductivity are improved.
[0041] From the viewpoint of the balance between ion conductivity and electron conductivity, the mass ratio of the carbon material to the lanthanoid fluoride doped with the alkaline earth metal fluoride is preferably 3 mass % or more and 20 mass % or less.
[0042] The content of the composite of lanthanum fluoride and carbon material in the negative electrode layer is preferably 60% by mass or more and 70% by mass or less. If the content of the composite of lanthanum fluoride and carbon material in the negative electrode layer is 60% by mass or more and 70% by mass or less, the discharge capacity of the fluoride ion secondary battery of this embodiment is improved.
[0043] (Method for producing a composite of lanthanide fluoride and carbon material)
[0044] The method for manufacturing a composite of lanthanide fluoride and carbon material (hereinafter also referred to as composite) includes: a first step of obtaining a lanthanide fluoride-alkaline earth metal fluoride mixed powder; a second step of mixing the lanthanide fluoride-alkaline earth metal fluoride mixed powder with a carbon material to obtain a composite precursor; and a third step of calcining the composite precursor to obtain a composite.
[0045] The first step is to mix the lanthanide fluoride and the alkaline earth metal fluoride to obtain a lanthanide fluoride-alkaline earth metal fluoride mixed powder. That is, by mixing the lanthanide fluoride and the alkaline earth metal fluoride, the solid phase diffusion distance of the elements derived from the lanthanide fluoride and the alkaline earth metal fluoride can be shortened during calcination. In addition, after calcination, a lanthanide fluoride-alkaline earth metal fluoride mixed powder can be obtained in which the crystal structure of the lanthanide fluoride and the alkaline earth metal fluoride remains.
[0046] The method for mixing the lanthanoid fluoride and the alkaline earth metal fluoride is not particularly limited, and either a dry method or a wet method may be used. For example, a method of mixing using a mortar may be mentioned.
[0047] Furthermore, the conditions such as temperature and time for mixing the lanthanoid fluoride and the alkaline earth metal fluoride can be appropriately set.
[0048] In addition, in the first step, the lanthanide fluoride-alkaline earth metal fluoride mixed powder may be pulverized.
[0049] Examples of a method for pulverizing the lanthanoid fluoride-alkaline earth metal fluoride mixed powder include a method of pulverizing using a ball mill.
[0050] The second step is a step of mixing the lanthanide fluoride-alkaline earth metal fluoride mixed powder obtained in the first step with a carbon material to obtain a composite precursor.
[0051] The method for producing the composite body is to perform the second step in the pre-stage of the third step, and pre-mix the carbon material in the lanthanide fluoride-alkaline earth metal fluoride mixed powder, thereby obtaining a composite body precursor in which the carbon material is arranged on the surface of the lanthanide fluoride-alkaline earth metal fluoride mixed powder.
[0052] Therefore, in the third step, by calcining the composite precursor, a composite in which at least a part of the surface of the lanthanide fluoride particles doped with the alkaline earth metal fluoride is coated with the carbon material is obtained.
[0053] In addition, in the second step, a carbon material is arranged on the surface of the lanthanide fluoride-alkaline earth metal fluoride mixed powder, thereby suppressing the grain growth of the lanthanide fluoride-alkaline earth metal fluoride mixed powder and the coarsening of the particle size caused by the fusion of the particle interfaces during the crystallization process in the third step, thereby obtaining a composite that roughly maintains the particle size of the lanthanide fluoride-alkaline earth metal fluoride mixed powder.
[0054] In the second step, the method for mixing the lanthanide fluoride-alkaline earth metal fluoride mixed powder and the carbon material is not particularly limited, and either a dry method or a wet method may be used, and for example, a method of mixing using a mortar may be used.
[0055] Furthermore, when mixing the lanthanoid fluoride-alkaline earth metal fluoride mixed powder and the carbon material, shearing is preferably applied.
[0056] Furthermore, the conditions such as the temperature for mixing the lanthanoid fluoride-alkaline earth metal fluoride mixed powder and the carbon material can be appropriately set.
[0057] Furthermore, in the second step, the composite precursor may be pulverized.
[0058] Examples of a method for pulverizing the composite precursor include a method of pulverizing using a ball mill and a method of pulverizing using a mortar.
[0059] The third step is a step of calcining the composite precursor obtained in the second step to obtain a composite.
[0060] In the second step, a composite precursor is obtained in which a carbon material is arranged on the surface of the lanthanide fluoride-alkaline earth metal fluoride mixed powder. As a result, during the crystallization process in the third step, the particle growth of the lanthanide fluoride-alkaline earth metal fluoride mixed powder and the coarsening of the particle size caused by the fusion of the particle interfaces are suppressed. As a result, a composite is obtained in which the particle size of the composite precursor is roughly maintained.
[0061] Furthermore, the conditions for calcining the composite precursor can be appropriately set.
[0062] In addition, in the third step, the composite may be pulverized.
[0063] Examples of a method for pulverizing the composite include a method of pulverizing the composite using a mortar.
[0064] (Solid Electrolyte)
[0065] The solid electrolyte preferably contains nanoparticles of at least one of BaCaF 4 and SrCaF 4 . This makes it easy to ensure an ion conduction path, and the discharge capacity of the fluoride ion secondary battery of this embodiment is improved.
[0066] The particle diameter of the nanoparticles of at least one of BaCaF 4 and SrCaF 4 is, for example, not less than 30 nm and not more than 200 nm.
[0067] From the viewpoint of the balance between ion conductivity and defluorination potential, the mass ratio of BaCaF 4 and SrCaF 4 to the total amount of cerium fluoride doped with alkaline earth metal fluoride is preferably 0.36 or more and 0.92 or less.
[0068] The solid electrolyte may further include solid electrolytes other than BaCaF 4 and SrCaF 4 .
[0069] The solid electrolyte other than BaCaF 4 and SrCaF 4 is not particularly limited as long as it is a solid electrolyte that can be used for a fluoride ion secondary battery.
[0070] [Positive electrode layer]
[0071] The positive electrode layer contains a positive electrode active material, and may further contain a conductive auxiliary agent, a solid electrolyte, and the like.
[0072] (Positive electrode active material)
[0073] The positive electrode active material contains a composite fluoride of copper and a fluorine compound, so that the discharge capacity of the fluoride ion secondary battery is improved.
[0074] As fluorine compounds, there are no particular limitations as long as they have ion conductivity, and examples thereof include lead fluoride (PbF2), tin fluoride (SnF2), bismuth fluoride (BiF3), lanthanum fluoride (LaF3), cerium fluoride (CeF3), sodium fluoride (NaF), potassium fluoride (KF), barium fluoride (BaF2), etc., and two or more thereof may be used in combination. Among these, sodium fluoride (NaF), potassium fluoride (KF) and barium fluoride (BaF2) are preferred.
[0075] The content of copper in the composite fluoride of copper and a fluorine compound is preferably 40 at% to 70 at%, more preferably 50 at% to 60 at%. If the content of copper in the composite fluoride of copper and a fluorine compound is 40 at% to 70 at%, the discharge capacity of the fluoride ion secondary battery is improved.
[0076] The particle size of the composite fluoride of copper and fluorine compound is preferably 100 nm or less, more preferably 50 nm or less. If the particle size of the composite fluoride of copper and fluorine compound is 50 nm or less, the diffusion distance of fluoride ions is short, so the utilization rate of the positive electrode active material is improved.
[0077] In terms of the balance between ion conductivity and electron conductivity, the content of the composite fluoride of copper and a fluorine compound in the positive electrode layer is preferably 25 mass % to 70 mass %, more preferably 50 mass % to 68 mass %.
[0078] The positive electrode active material may further contain a positive electrode active material other than the composite fluoride of copper and a fluorine compound.
[0079] The positive electrode active material other than the composite fluoride of copper and a fluorine compound is not particularly limited as long as it is a negative electrode active material that can be used in a fluoride ion secondary battery.
[0080] (Method for producing composite fluoride of copper and fluorine compound)
[0081] The method for producing a composite fluoride of copper and a fluorine compound includes an aerosol process of atomizing and spraying a raw material melt containing copper and a fluorine compound under reduced pressure.
[0082] Specifically, first, copper and fluorine compounds are weighed and mixed to obtain a raw material mixed powder. At this time, the raw material mixed powder may be subjected to classification treatment as required. Then, the raw material mixed powder is melted by thermal plasma or the like to form a raw material melt, and the raw material melt is atomized and sprayed into a chamber in a reduced pressure environment. Then, the atomized raw material melt is cooled and nano-particleized to obtain a composite fluoride of copper and fluorine compounds.
[0083] (Conductive additive)
[0084] Examples of the conductive additive include carbon materials and the like.
[0085] The carbon material may also be carbon black.
[0086] Examples of carbon black include furnace black, Ketjen black, and acetylene black, and two or more types of carbon black may be used in combination.
[0087] (Solid Electrolyte)
[0088] Examples of the solid electrolyte include lanthanide fluorides doped with alkaline earth metal fluorides, BaCaF 4 , PbSnF 4 , etc. Among these, lanthanide fluorides doped with alkaline earth metal fluorides are preferred in terms of ion conductivity and withstand voltage.
[0089] As the lanthanoid fluoride doped with an alkaline earth metal fluoride, the same compounds as the lanthanoid fluoride doped with an alkaline earth metal fluoride used as the above-mentioned negative electrode active material can be used.
[0090] In addition, the lanthanoid fluoride doped with alkaline earth metal fluoride may be composited with a carbon material in the same manner as the lanthanoid fluoride doped with alkaline earth metal fluoride used as the negative electrode active material.
[0091] In this case, it is preferred to wet-mix the composite fluoride of copper and fluorine compounds and the composite of lanthanide fluoride and carbon material doped with alkaline earth metal fluoride and then dry to produce the positive electrode layer. Thus, the aggregation of the composite fluoride of copper and fluorine compounds and the composite of lanthanide fluoride and carbon material doped with alkaline earth metal fluoride is suppressed, so the charge and discharge capacity of the fluoride secondary battery of this embodiment is improved.
[0092] Examples of the solvent used when wet-mixing the composite fluoride of copper and a fluorine compound and the composite of lanthanoid fluoride doped with alkaline earth metal fluoride and a carbon material include cyclohexane and dimethyl carbonate.
[0093] The particle size of the composite of lanthanoid fluoride and carbon material is preferably 10 μm or less, more preferably 5 μm or less. When the particle size of the composite of lanthanoid fluoride and carbon material is 10 μm or less, ion conductivity and electron conductivity are improved.
[0094] From the viewpoint of the balance between ion conductivity and electron conductivity, the mass ratio of the carbon material to the lanthanoid fluoride doped with the alkaline earth metal fluoride is preferably 3 mass % or more and 20 mass % or less.
[0095] [Solid electrolyte layer]
[0096] The solid electrolyte layer contains BaCaF 4 . Therefore, the energy density of the fluoride ion secondary battery of this embodiment is improved.
[0097] The solid electrolyte layer preferably contains nanoparticles of BaCaF 4 . This improves the energy density of the fluoride ion secondary battery of this embodiment.
[0098] The particle diameter of the nanoparticles of at least one of BaCaF 4 and SrCaF 4 is, for example, not less than 30 nm and not more than 200 nm.
[0099] The solid electrolyte layer may further contain a solid electrolyte other than BaCaF4.
[0100] The solid electrolyte other than BaCaF 4 is not particularly limited as long as it is a solid electrolyte that can be used for a fluoride ion secondary battery.
[0101] [Positive electrode current collector and negative electrode current collector]
[0102] Examples of the positive electrode current collector include gold foil and the like. Examples of the negative electrode current collector include gold foil and the like.
[0103] [Example]
[0104] Hereinafter, examples of the present invention will be described, but the present invention is not limited to the examples.
[0105] <Example 1>
[0106] An all-solid fluoride ion secondary battery was produced by the following method. Unless otherwise specified, each step was carried out in a purge-type glove box DBO-1.5B (manufactured by Miwa Seisakusho) equipped with an argon gas circulation purification device.
[0107] [Ce 0.95 Ba 0.05 F 2.95 -Production of AB complex]
[0108] (First step)
[0109] After weighing 8.598 g of CeF3 powder (manufactured by Sigma-Aldrich; purity 99.99%) and 0.402 g of BaF2 powder (manufactured by High Purity Chemical Research Institute; purity 99.9%), use an agate mortar and pestle to mix for 5 to 10 minutes to obtain a CeF3-BaF2 mixed powder.
[0110] The CeF3-BaF2 mixed powder and 20 silicon nitride grinding balls (manufactured by Fritsch) with a diameter of 10 mm were placed in a premium line PL-7 dedicated container (manufactured by Fritsch) which was an 80 cc silicon nitride ball mill pot, and then sealed.
[0111] After the sealed ball mill pot was carried out of the glove box, a pulverization treatment was performed using a ball mill. At this time, the pulverization treatment conditions were as described below.
[0112] Speed: 800rpm
[0113] Crushing time: 60 minutes
[0114] Crushing times: 40 times
[0115] Rest time during crushing process: 5 minutes
[0116] Rotation reversing (reverse): open (ON)
[0117] After the ball mill tank was moved into the glove box, the CeF3-BaF2 mixed powder was recovered from the inside of the ball mill tank.
[0118] (Step 2)
[0119] Using an agate mortar and pestle, 3.08 g of CeF3-BaF2 mixed powder and 0.22 g of DENKABLACK (manufactured by Denka Company Limited), which is acetylene black (AB), were mixed to obtain CeF3-BaF2. 0.95 Ba 0.05 F 2.95 -AB complex precursor.
[0120] Ce 0.95 Ba 0.05 F2.95 -AB complex precursor, 20 10mm diameter zirconium oxide grinding balls (manufactured by Feichi), and 20 10mm diameter silicon nitride grinding balls (manufactured by Feichi) were placed in an advanced production line PL-7 dedicated container (manufactured by Feichi) which was an 80cc silicon nitride ball mill pot and then sealed.
[0121] After the sealed ball mill pot was carried out of the glove box, a pulverization treatment was performed using a ball mill. At this time, the pulverization treatment conditions were as described below.
[0122] Speed: 800rpm
[0123] Crushing time: 60 minutes
[0124] Crushing times: 40 times
[0125] Rest time during crushing process: 5 minutes
[0126] Rotation reversing: open (ON)
[0127] After the ball mill is moved into the glove box, Ce is recovered from the inside of the ball mill. 0.95 Ba 0.05 F 2.95 -AB complex precursor. Using an agate mortar and pestle, the recovered Ce 0.95 Ba 0.05 F 2.95 -AB complex precursor is crushed for 5 to 10 minutes.
[0128] (Third step)
[0129] Ce 0.95 Ba 0.05 F 2.95 The AB composite precursor was transferred into an alumina crucible and calcined using a small electric furnace KSL-1100X (manufactured by MTI) to obtain Ce 0.95 Ba 0.05 F 2.95 -AB complex. At this time, the calcination conditions are as described below.
[0130] Argon flow rate: 300cc / min (minute)
[0131] Heating rate: 184℃ / h (hour)
[0132] Maximum temperature reached: 1100℃
[0133] Holding time at maximum temperature: 1 hour
[0134] Cooling speed: no control
[0135] Cooling method: Natural cooling
[0136] Recovery of Ce from the inside of an alumina crucible 0.95 Ba 0.05 F 2.95 -AB complex, and then pulverize it for 5 to 10 minutes using an agate mortar and pestle.
[0137] [Production of BaCaF4]
[0138] (Premixed)
[0139] After weighing 690 mg of barium fluoride powder (produced by High-Jun Chemical Research Institute; purity 99%) and 310 mg of calcium fluoride powder (produced by High-Jun Chemical Research Institute; purity 99.9%), use an agate mortar and pestle to pre-mix for about 1 hour to obtain a BaF2-CaF2 mixed powder.
[0140] (Aerosol process)
[0141] After the closed powder hopper filled with the BaF2-CaF2 mixed powder was carried out to the outside of the glove box, it was connected to the high-frequency induction thermal plasma nanoparticle synthesis device TP-40020NPS (manufactured by JEOL).
[0142] Argon gas is supplied to the plasma torch, and the BaF2-CaF2 mixed powder is melted by thermal plasma to form a BaF2-CaF2 melt, and then the BaF2-CaF2 melt is atomized and sprayed into a chamber in a reduced pressure environment. The BaF2-CaF2 melt atomized and sprayed into the chamber is cooled and nano-particled to become BaCaF4. Next, the BaCaF4 is captured by the exhaust filter downstream of the device. Next, the upstream and downstream of the exhaust filter are cut off by a valve, and then the BaCaF4 powder is carried into the glove box to recover the BaCaF4 powder.
[0143] [Preparation of powder composition for negative electrode layer]
[0144] Ce 0.95 Ba 0.05 F 2.95 636 mg of the AB complex, 364 mg of BaCaF4 and 40 g of silicon nitride grinding balls (manufactured by Feichi) with a diameter of 2 mm were placed in a 45 cc silicon nitride ball mill pot of Advanced Line PL-7 dedicated container (manufactured by Feichi), and then sealed.
[0145] After the sealed ball mill pot was carried out of the glove box, a pulverization treatment was performed using a ball mill. At this time, the pulverization treatment conditions were as described below.
[0146] Speed: 200rpm
[0147] Crushing time: 15 minutes
[0148] Crushing times: 10 times
[0149] Rest time during crushing process: 5 minutes
[0150] Rotation reversing: open (ON)
[0151] After the ball mill pot was moved into the glove box, the negative electrode layer powder composition was recovered from the inside of the ball mill pot.
[0152] [Preparation of Cu-BaF2 composite fluoride]
[0153] (Premixed)
[0154] After weighing 480 mg of Cu metal powder with an average particle size of 1 μm (manufactured by High Pure Chemical Research Institute; purity 99.99%) and 190 mg of barium fluoride powder (manufactured by High Pure Chemical Research Institute; purity 99.9%), use an agate mortar and pestle to pre-mix for about 1 hour to obtain a Cu-BaF2 mixed powder.
[0155] (Aerosol process)
[0156] The closed powder hopper filled with the Cu-BaF2 mixed powder was carried out of the glove box and then connected to a high-frequency induction thermal plasma nanoparticle synthesis device TP-40020NPS (manufactured by JEOL Ltd.).
[0157] Argon gas is supplied to the plasma torch, and the Cu-BaF2 mixed powder is melted by thermal plasma to form a Cu-BaF2 melt, and then the Cu-BaF2 melt is atomized and sprayed into a chamber in a reduced pressure environment. The Cu-BaF2 melt atomized and sprayed into the chamber is cooled and nano-particled to become a Cu-BaF2 composite fluoride. Then, the Cu-BaF2 composite fluoride is captured by an exhaust filter downstream of the device. Then, the upstream and downstream of the exhaust filter are cut off by a valve, and the Cu-BaF2 composite fluoride is moved into the glove box to recover the Cu-BaF2 composite fluoride.
[0158] [Preparation of Powder Composition for Positive Electrode Layer]
[0159] 670 mg of Cu-BaF2 composite fluoride and Ce 0.95 Ba 0.05 F 2.95 330 mg of the AB complex, 10 g of cyclohexane and 40 g of silicon nitride grinding balls (manufactured by Feichi) with a diameter of 2 mm were placed in a 45 cc silicon nitride ball mill pot of Advanced Line PL-7 dedicated container (manufactured by Feichi), and then sealed.
[0160] After the sealed ball mill pot was carried out of the glove box, a pulverization treatment was performed using a ball mill. At this time, the pulverization treatment conditions were as described below.
[0161] Speed: 200rpm
[0162] Crushing time: 15 minutes
[0163] Crushing times: 40 times
[0164] Rest time during crushing process: 5 minutes
[0165] Rotation reversing: open (ON)
[0166] After the contents of the ball mill pot were vacuum dried, the pot was moved into a glove box to recover the powder composition for the positive electrode layer.
[0167] [Powder for solid electrolyte layer]
[0168] As the solid electrolyte layer powder, BaCaF4 used in the preparation of the negative electrode layer powder composition was used.
[0169] [Fabrication of all-solid fluoride ion secondary battery]
[0170] A tablet forming machine was used to press at a pressure of 40 MPa to produce a cylindrical pellet-type monomer (pellet cell) formed by pressing powder. Specifically, a 20 μm thick gold foil (manufactured by Nilaco; purity 99.99%) as a negative electrode collector, 30 mg of a powder composition for a negative electrode layer, 20 mg of a solid electrolyte layer powder, 20 mg of a positive electrode layer powder composition, and a 20 μm thick gold foil (manufactured by Nilaco; purity 99.99%) as a positive electrode collector were put into a tablet forming machine in this order to produce a pellet-type monomer.
[0171] <Comparative Example 1>
[0172] An all-solid fluoride ion secondary battery was prepared in the same manner as in Example 1 except that the negative electrode layer powder, the solid electrolyte layer powder, and the all-solid fluoride ion secondary battery were prepared as follows.
[0173] [Preparation of powder for negative electrode layer (PbSnF4-AB complex)]
[0174] 63.7 mass % of lead fluoride powder (manufactured by High Purity Chemical), 29.6 mass % of tin fluoride powder (manufactured by High Purity Chemical), and 6.7 mass % of electrochemical black (manufactured by Electrochemical) as AB were mixed in a ball mill and calcined at 400°C for 1 hour in an argon atmosphere to prepare a PbSnF4-AB complex.
[0175] [Powder for solid electrolyte layer (Ce 0.95 Ba 0.05 F 2.95 )
[0176] (First step)
[0177] After weighing 8.598 g of CeF3 powder (manufactured by Sigma-Aldrich; purity 99.99%) and 0.402 g of BaF2 powder (manufactured by High Purity Chemical Research Institute; purity 99.9%), use an agate mortar and pestle to mix for 5 to 10 minutes to obtain a CeF3-BaF2 mixed powder.
[0178] The CeF3-BaF2 mixed powder and 20 silicon nitride grinding balls (manufactured by Feichi) with a diameter of 10 mm were placed in an Advanced Line PL-7 dedicated container (manufactured by Feichi) which was an 80 cc silicon nitride ball mill pot, and then sealed.
[0179] After the sealed ball mill pot was carried out of the glove box, a pulverization treatment was performed using a ball mill. At this time, the pulverization treatment conditions were as described below.
[0180] Speed: 800rpm
[0181] Crushing time: 60 minutes
[0182] Crushing times: 40 times
[0183] Rest time during crushing process: 5 minutes
[0184] Rotation reversing: open (ON)
[0185] After the ball mill tank was moved into the glove box, the CeF3-BaF2 mixed powder was recovered from the inside of the ball mill tank.
[0186] (Second step)
[0187] The CeF3-BaF2 mixed powder was transferred into an alumina crucible and calcined using a small electric furnace KSL-1100X (manufactured by MTI) to obtain Ce 0.95 Ba 0.05 F 2.95 At this time, the calcination conditions are as follows.
[0188] Argon flow rate: 300cc / min (minute)
[0189] Heating rate: 184℃ / h (hour)
[0190] Maximum temperature reached: 1100℃
[0191] Holding time at maximum temperature: 1 hour
[0192] Cooling speed: no control
[0193] Cooling method: Natural cooling
[0194] Recovery of Ce from the inside of an alumina crucible 0.95 Ba 0.05 F 2.95 Then, use an agate mortar and pestle to grind for 5 to 10 minutes.
[0195] [Fabrication of all-solid fluoride ion secondary battery]
[0196] A tablet forming machine was used to press at a pressure of 40 MPa to produce a cylindrical particle-type monomer formed by pressing powder. Specifically, an aluminum foil with a thickness of 20 μm (manufactured by Nilaca; purity 99+%) as a negative electrode collector, 30 mg of powder for the negative electrode layer, 150 mg of powder for the solid electrolyte layer, 20 mg of the powder composition for the positive electrode layer, and a gold foil with a thickness of 20 μm (manufactured by Nilaca; purity 99.99%) as a positive electrode collector were put into the tablet forming machine in this order to produce a particle-type monomer.
[0197] [Particle size of powder]
[0198] (Particle size of Cu-BaF2 composite fluoride and BaCaF4)
[0199] The specific surface area of the powder was measured using a fully automatic specific surface area measuring apparatus, Macsorb HM model-1208 (manufactured by Mountech), and the particle size was calculated from the specific surface area and true density of the powder.
[0200] As a result, the particle sizes of Cu-BaF2 composite fluoride and BaCaF4 were 18 nm and 110 nm, respectively.
[0201] (Ce 0.95 Ba 0.05 F 2.95 -AB complex, Ce 0.95 Ba 0.05 F 2.95 and the particle size of PbSnF4-AB complex)
[0202] The powder was photographed using a scanning electron microscope SU-6600 (manufactured by Hitachi High-technologies), and the length of the powder in the scanning electron microscope (SEM) image in multiple fields of view was measured to obtain the particle size.
[0203] As a result, Ce 0.95 Ba 0.05 F 2.95 -AB complex, Ce 0.95 Ba 0.05 F 2.95 The particle sizes of the PbSnF4-AB complex are 50μm, 100μm and 100μm respectively.
[0204] [Charge and discharge test]
[0205] A constant current charge and discharge test of the all-solid fluoride ion secondary battery was performed. Specifically, a potentiogalvanostat device SI1287 / 1255B (manufactured by Solartron) was used, and the current during charge and discharge was set to 0.04 mA in a vacuum environment at 140°C. In Example 1, an upper limit voltage of 3.8 V and a lower limit voltage of 1.0 V were set, and in Comparative Example 1, an upper limit voltage of 1.3 V and a lower limit voltage of 0.3 V were set. The constant current charge and discharge test was performed starting from charging.
[0206] exist Figure 1 Graphs showing the initial charge and discharge curves of the all-solid fluoride ion secondary batteries of Example 1 and Comparative Example 1.
[0207] Depend on Figure 1 It can be seen that the all-solid fluoride ion secondary battery of Example 1 has a higher charge and discharge capacity than the all-solid fluoride ion secondary battery of Comparative Example 1.
[0208] Table 1 shows the evaluation results of the discharge capacity, 50% discharge voltage, and energy density of the all-solid fluoride ion secondary batteries of Example 1 and Comparative Example 1.
[0209] [Table 1]
[0210] Example 1 Comparative Example 1 Discharge capacity[mAh] 4.37 2.20 50% discharge voltage [V] 2.7 0.6 Energy density [Wh / kg] 169 6
[0211] As can be seen from Table 1, the all-solid fluoride ion secondary battery of Example 1 has higher charge and discharge capacity, 50% discharge voltage and energy density than the all-solid fluoride ion secondary battery of Comparative Example 1.
Claims
1. A fluoride ion secondary battery comprising a positive electrode layer, a solid electrolyte layer and a negative electrode layer, The positive electrode layer contains a positive electrode active material. The positive electrode active material comprises a composite fluoride of copper and a fluorine compound. The content of copper in the composite fluoride is 40 at% or more and 70 at% or less, The fluorine compound is one or more compounds selected from the group consisting of PbF2, SnF2, BiF3, LaF3, CeF3, NaF, KF, and BaF2, The solid electrolyte layer comprises BaCaF4, The negative electrode layer comprises a negative electrode active material, a conductive aid and a solid electrolyte. The negative electrode active material comprises lanthanide fluoride doped with alkaline earth metal fluoride, The alkaline earth metal fluoride is one or more compounds selected from the group consisting of CaF2, SrF2 and BaF2, The lanthanide fluoride is one or more compounds selected from the group consisting of LaF3, CeF3, SmF3 and NdF3, The conductive additive comprises a carbon material. The solid electrolyte contained in the negative electrode layer includes at least one of BaCaF4 and SrCaF4, The lanthanide fluoride doped with alkaline earth metal fluoride and the carbon material are composited. The content of the lanthanide fluoride element and the carbon material doped with the alkaline earth metal fluoride in the negative electrode layer is 60% by mass or more and 70% by mass or less, The mass ratio of the carbon material to the lanthanide fluoride doped with the alkaline earth metal fluoride is 3 mass % or more and 20 mass % or less.
2. The fluoride ion secondary battery according to claim 1, wherein The lanthanide fluoride doped with alkaline earth metal fluoride is selected from La 0.9 Ba 0.1 F 2.9 、Ce 0.95 Ba 0.05 F 2.95 、Ce 0.95 Sr 0.05 F 2.95 Ce 0.95 Ca 0.05 F 2.95 More than one compound in the group consisting of.
3. The fluoride ion secondary battery according to claim 1, wherein The solid electrolyte included in the negative electrode layer includes nanoparticles of at least one of BaCaF 4 and SrCaF 4 .
4. The fluoride ion secondary battery according to claim 1, wherein The solid electrolyte layer contains nanoparticles of BaCaF4.
Citation Information
Patent Citations
Positive electrode active material for fluoride ion secondary batteries, positive electrode using said active material, fluoride ion secondary battery, and method for producing said active material
WO2019187942A1
Fluoride ion battery and method for producing fluoride ion battery
CN108075176A
A method for manufacturing a nanoparticle material and a fluoride ion battery
CN111263994A